2020
DOI: 10.1126/science.aba9102
|View full text |Cite
|
Sign up to set email alerts
|

Structures of cell wall arabinosyltransferases with the anti-tuberculosis drug ethambutol

Abstract: The arabinosyltransferases EmbA, EmbB, and EmbC are involved in Mycobacterium tuberculosis cell wall synthesis and are recognized as targets for the anti-tuberculosis drug ethambutol. In this study, we determined cryo–electron microscopy and x-ray crystal structures of mycobacterial EmbA-EmbB and EmbC-EmbC complexes in the presence of their glycosyl donor and acceptor substrates and with ethambutol. These structures show how the donor and acceptor substrates bind in the active site and how ethambutol inhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 60 publications
(90 reference statements)
2
98
0
2
Order By: Relevance
“…2B, 2C and S3C), which may help to stabilize the entire PD. Not surprisingly, this overall folding represented by EmbB 2 -AcpM 2 complex agrees well with that of the previously reported Emb proteins (Zhang et al, 2020).…”
Section: Two Distinct States Of Embb 2 -Acpm 2 Complexsupporting
confidence: 91%
See 2 more Smart Citations
“…2B, 2C and S3C), which may help to stabilize the entire PD. Not surprisingly, this overall folding represented by EmbB 2 -AcpM 2 complex agrees well with that of the previously reported Emb proteins (Zhang et al, 2020).…”
Section: Two Distinct States Of Embb 2 -Acpm 2 Complexsupporting
confidence: 91%
“…EmbB catalyzes the penultimate step of AG synthesis. We have previously reported that EmbB functions in a coordinating way with EmbA (Zhang et al, 2020), nevertheless, our cell-free assay has confirmed that purified EmbB alone is functional using NV6 as acceptor. Thus, it can be inferred that EmbB may play dual roles in cells, by either forming a homodimer or a heterodimer with EmbA, depending on the physiological concentration of these proteins.…”
Section: Research Articlesupporting
confidence: 46%
See 1 more Smart Citation
“…Comparison with heterodimeric Emb structures. Recently, the structures of heterodimeric M. smegmatis and M. tuberculosis EmbA, EmbB, and EmbC were determined 12 . M. smegmatis EmbB was solved as a dimer with EmbA, bound to either ethambutol or di-arabinofuranose ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EmbB and EmbC have mutations known to lead to ethambutol resistance 9 , while a clear effect of the drug on EmbA activity has not been established 10 . The dearth of atomic models of these proteinsonly a high resolution structure of the C-terminal soluble domain of EmbC is available 11 -has thus far hindered our understanding of the catalytic action and drug resistance mechanisms of these proteins, although this situation has been recently remedied to a certain extent by eludication of structures of the EmbA-EmbB and EmbC-EmbC dimer complexes 12 . Here, we report the structure of M. smegmatis EmbB to 3.3-Å resolution, providing insights on substrate binding and reaction mechanism.…”
mentioning
confidence: 99%